1999
DOI: 10.1161/01.atv.19.1.122
|View full text |Cite
|
Sign up to set email alerts
|

LDL Isolated From Greek Subjects on a Typical Diet or From American Subjects on an Oleate-Supplemented Diet Induces Less Monocyte Chemotaxis and Adhesion When Exposed to Oxidative Stress

Abstract: Abstract-The mechanisms underlying the cardiovascular benefits of Mediterranean-style diets are not fully understood.The high content of monounsaturated fatty acids in Mediterranean-style diets derived from oleate-rich olive oil may be beneficial in reducing low density lipoprotein (LDL) oxidation and its subsequent development of atherogenic properties. This study sought to assess the proinflammatory potential of LDL isolated from subjects consuming a diet naturally rich in olive oil. LDL was isolated from 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 49 publications
2
48
0
2
Order By: Relevance
“…LDL enriched in oleic acid promote less monocyte chemotaxis, compared with linoleic acid-enriched LDL, when exposed to oxidation (Tsimikas et al, 1999). Esposito et al (2004) found a reduction in the inflammatory markers after a 2-year follow-up of patients with metabolic syndrome consuming a Mediterranean-type diet.…”
Section: Discussionmentioning
confidence: 99%
“…LDL enriched in oleic acid promote less monocyte chemotaxis, compared with linoleic acid-enriched LDL, when exposed to oxidation (Tsimikas et al, 1999). Esposito et al (2004) found a reduction in the inflammatory markers after a 2-year follow-up of patients with metabolic syndrome consuming a Mediterranean-type diet.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, extra virgin olive oil vs high oleic acid sun¯ower oil or re®ned olive oil also did not affect the in vitro susceptibility of LDL to oxidation in fasting plasma samples. Other human studies on the effect of olive oil on LDL oxidation addressed the effects of oleic acid rather than olive oil phenols per se (Reaven et al, 1991;Bonanome et al, 1992;Tsimikas et al, 1999). In vitro, the olive oil phenols hydroxytyrosol and oleuropein strongly inhibited LDL oxidation (Visioli et al, 1995;Visioli & Galli, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that the modulation of LDL fatty acid composition was responsible for the differences in adhesion and showed a significant negative correlation between monocyte adhesion to endothelial cells and the oleic acid content of LDL (Mata et al, 1996). Similarly, Tsimikas et al (1999) prepared and oxidized LDL from Greek and American subjects, with differing intakes of olive oil, and assessed monocyte chemotaxis induced by oxidised LDL. Induction of chemotaxis was 42% lower in Greeks compared to Americans and there was an inverse correlation between the OA content of LDL and monocyte chemotaxis, but a positive one between linoleic and AA and monocyte chemotaxis, suggesting that OA is anti-inflammatory and PUFA are pro-inflammatory (Tsimikas et al, 1999).…”
Section: Effects Of Olive Oil On Expression Of Adhesion Moleculesmentioning
confidence: 99%
“…Similarly, Tsimikas et al (1999) prepared and oxidized LDL from Greek and American subjects, with differing intakes of olive oil, and assessed monocyte chemotaxis induced by oxidised LDL. Induction of chemotaxis was 42% lower in Greeks compared to Americans and there was an inverse correlation between the OA content of LDL and monocyte chemotaxis, but a positive one between linoleic and AA and monocyte chemotaxis, suggesting that OA is anti-inflammatory and PUFA are pro-inflammatory (Tsimikas et al, 1999).…”
Section: Effects Of Olive Oil On Expression Of Adhesion Moleculesmentioning
confidence: 99%